Osgood-Schlatter disease and potential treatment - Wojcik, Bartlomiej; Fabis, Mateusz; Remjasz, Klaudia; Kuchnicka, Julia; Zadrożna, Karolina; Aleksandrowicz, Jakub; Siedlecki, Wojciech (Journal of Education, Health and Sport, 2022)
Background: Aseptic necrosis of the tibial tuberosity, also known as Osgood-Schlatter disease, is one of the more common causes of pain in the tibia area in children and adolescents. The pathology is much more common in boys than in girls. Young athletes, including training footballers, basketball players and volleyball players, as well as children who actively spend their free time are particularly exposed to the development of the disease. Material and methods: This paper was based on medical articles collected in PubMed , medical websites and books. The research has been done by looking through key words such as:’’ Osgood-Schlatter disease”,’’Osgood-Schlatter treatment” Results: Osgood-Schlatter disease is usually self-limiting. In the absence of symptom relief, there are operational methods, which, however, are ambiguous. Conclusions: Treatment of OSD patients and a challenge for healthcare professionals.